TINDAKAN PEMERINTAHAN DALAM PENANGGULANGAN PENAMBANGAN EMAS TANPA IZIN (PETI) DI KABUPATEN KUANTAN SINGINGI TAHUN 2017-2018 - Wahyuni, Fitri; ", Isril (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
PETI is an abbreviation of unlicensed gold mining,mining business conducted by individuals, groups of people or companies in which the operation has no permission.The problem in this research is to know how the local government action in response to PETI in Kuantan Singingi district in 2017-2018? The purpose of this research is to know what actions are performed by the government of Kuantan Singingi Regency in response to PETI in Kuantan Singingi District. This research is a descriptive study with a qualitative approach.The location of this research is done in Kuantan Singingi district. Data collection techniques are conducted with qualitative data analysis.The results concluded that the government action in the management of gold mining without permission (PETI) by the district government of Kuantan Singingi Regency year 2017-2018 not carried out with maximum. The authors hope from the results of this study can help enrich the information about the actions taken by the Government of Kuantan Singingi Regency.